ANALISIS KONDISI RUMAH SEKITAR RUMAH PENDERITA LEPTOSPIROSIS DI KOTA SURABAYA TAHUN 2018 (Di Kelurahan Babatan, Kecamatan Wiyung, Kota Surabaya, Jawa Timur) - Nadia Putri Ramadhani; Umi Rahayu; Imam Thohari (Poltekkes Kemenkes Surabaya, 2018)
A healthy home is needed so that the function and usefulness of the house can be fulfilled properly, one of which is protecting its inhabitants from infectious diseases. Leptospirosis is one of the zoonotic infectious diseases caused by Leptospira interrogans, a spirochaeta class that can be transmitted from animals to humans. The purpose of this research is to find out how the condition of the house around the house of leptospirosis patients house in Babatan Village, Wiyung Subdistrict, Surabaya City, East Java Year 2018.The results showed that there were 76 (96%) houses whose condition in the house was eligible and the remaining 3 (4%) houses were not eligible. The other three variables, namely environmental conditions outside the home, the existence of rats, and the existence of pets show eligible results of 45 (57%) homes and non-qualified 34 (43%) homes; 54 (68%) houses met the requirements and those who did not meet the requirements of 25 (32%) houses; 75 (95%) houses met the requirements and those who did not meet the requirements of 4 (5%) houses. Key words: House Condition, Leptospirosis.